Microsporidia parásitos de larvas de mosquito de la Costa Pacífica del Chocó - Zuluaga Juan S.; Weiser Jaroslav; Rojas William; Orduz Sergio (Caldasia)
Two genera of Microsporidia were found infecting mosquito larvae in three localities on the Pacific coast of Choco. Vavraia sp. (Microsporida: Pleistophoridae) was found in larvae of Wyeomyia circumcincta, W. simmsi and Anopheles albimanus collected from plants of the Bromeliacea family in Arusí y Joví. Amblyospora sp. (Microsporida: Amblyosporidae) was found parasitizingAedes angustivittatuslarvae COllectedfrom a terrestrial breeding pond in the locality of Nuqur. Morphology of the spores of the two parasites under light microscopy is described, as well as preliminary data on host range when exposed to laboratory rearad Aedes aegypti, Culex quinquefasciatus and Anopheles albimanus. Their rola in mosquito control is discussed. Se reportan dos géneros de microsporidia que parasitan larvas de mosquitos en criaderos naturales de tres localidades en la costa Pacffica Chocoana. Vavraia sp. (Microsporida: Pleistophoridae) parásita larvas de Wyeomyia circumcincta, de Wyeomya simmsi y de Anopheles neivai, recolectadas en las rosetas de especies de la familia Bromeliaceae en las localidades de Arusí y Joví. Amblyospora sp. (Microsporida: Amblyosporidae) parásita larvas deAedes angustivittatusde criaderos terrestres semipermanentes en la localidad de Nuquí. Se describe la morfología de estos dos microsporidia al microscopio óptico. Estudios preliminares de infección en larvas de Aedes aegypti, Culex quinquefasciatus yAnopheles albimanus, criadas en laboratorio, indican que Vavraia sp. infecta las tres especies, con preferencia a Culex quinquefasciatus. Las larvas expuestas a esporas de Amblyospora sp. no presentaron infección. Se discute el posible papel de estos dos géneros en el control de las poblaciones de mosquitos.